Nonlinear studies on the effect of non-uniform heat generation/absorption on hydromagnetic flow of nanofluid over a vertical plate - Hakeem, Abdul Kafoor Abdul Kafoor Abdul; Ganga, Bhose; Ansari, Sait Mohamed Yusuff Mohamed Yusuff; Ganesh, Nagaraj Vishnu Vishnu; Rahman, Mohammad Mansur Mansur (Nonlinear Analysis: Modelling and Control, 2017)
The analytical and numerical studies are performed to investigate the non-uniform heat generation/absorption effect on the boundary layer flow of an incompressible, electrically conducting nanofluid over a vertical plate in the presence of thermal radiation. The highly nonlinear governing equations along with the boundary conditions are converted into ordinary differential equations by appropriate similarity transformations. The transformed highly nonlinear ordinary differential equations are solved both analytically and numerically using homotopy analysis method and fourth order Runge–Kutta method with shooting technique respectively, for the various values of physical parameters. The results show that the presence of both space and temperature dependent heat generation enhances the velocity and temperature profiles and reduces the solid volume fraction of nanofluid profile. Comparison between present analytical and numerical results is found to be good.
Keywords: homotopy analysis method; hydromagnetic flow; nanofluid; non-uniform heat generation/absorption; thermal radiation; vertical plate